Anty-Gombrowicz i Różewicz - Skrendo, Andrzej (Przestrzenie Teorii, 2014)
This article deals with Tadeusz Różewicz’s opinions of Witold Gombrowicz’s creations. The author compares both writers’ views on literature, especially poetry and theater. He states that Różewicz has created a character who can be called “Anti-Gombrowicz”. The author reveals how Różewicz thought up this peculiar concept and then tried to release himself from it.